2009
DOI: 10.1029/2009gl038569
|View full text |Cite
|
Sign up to set email alerts
|

Vertical motion in the upper ocean from glider and altimetry data

Abstract: This study represents a first attempt to combine new glider technology data with altimetry measurements to understand the upper ocean dynamics and vertical exchanges in areas with intense horizontal density gradients. In July 2008, just two weeks after Jason‐2 altimeter was launched, a glider mission took place along a satellite track in the Alboran Sea (Western Mediterranean). The mission was designed to be almost simultaneous with the satellite passage. Dynamic height from glider reveals a sharp gradient (∼1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 36 publications
1
61
0
Order By: Relevance
“…Though more complicated techniques such as the semi-geostrophic omega equation (Viúdez and Dritchel, 2004) have been proposed, the most used technique is based on the solution of the quasi-geostrophic (QG) omega equation (e.g. Tintoré et al, 1991;Buongiorno Nardelli et al, 2001;Pascual et al, 2004;Ruiz et al, 2009), which has already been shown to give reasonable estimates of the vertical velocities compared to primitive equation models (Pinot et al, 1996).…”
Section: Qg Vertical Velocity Estimationmentioning
confidence: 99%
See 4 more Smart Citations
“…Though more complicated techniques such as the semi-geostrophic omega equation (Viúdez and Dritchel, 2004) have been proposed, the most used technique is based on the solution of the quasi-geostrophic (QG) omega equation (e.g. Tintoré et al, 1991;Buongiorno Nardelli et al, 2001;Pascual et al, 2004;Ruiz et al, 2009), which has already been shown to give reasonable estimates of the vertical velocities compared to primitive equation models (Pinot et al, 1996).…”
Section: Qg Vertical Velocity Estimationmentioning
confidence: 99%
“…On the other hand, simplified diagnostic models can be applied to retrieve the vertical velocity field from both 2-D and/or 3-D estimates of geostrophic currents and density fields (e.g. Tintoré et al, 1991;Allen and Smeed, 1996;Buongiorno Nardelli et al, 2001;Pascual et al, 2004;Isern-Fontanet et al, 2008;Ruiz et al, 2009).…”
Section: B Buongiorno Nardelli Et Al: Towards High Resolution Mappimentioning
confidence: 99%
See 3 more Smart Citations